Timekeepers - Garfield, Simon (Canongate, 2016)
Not so long ago we timed our lives by the movement of the sun. These days our time arrives atomically and insistently, and our lives are propelled by the notion that we will never have enough of the one thing we crave the most. How have we come to be dominated by something so arbitrary? The compelling stories in this book explore our obsessions with time. Timekeepers is a vivid exploration of the ways we have perceived, contained and saved time over the last 250 years, narrated in the highly inventive and entertaining style that bestselling author Simon Garfield is fast making his own. As managing time becomes the greatest challenge we face in our lives, this multi-layered history helps us tackle it in a sparkling new light. --